Muscle mass loss is associated with physical dysfunction in patients with early rheumatoid arthritis - Pan, Jie; Zou, Yao-Wei; Zhu, Ying-Ying; Lin, Jian-Zi; Wu, Tao; Yang, Ze-Hong; Zhang, Xue-Pei; Zhang, Qian; Zheng, Hu-Wei; He, Xiao-Ling; Cheng, Wan-Mei; Ma, Jian-Da; et al. (Frontiers in Nutrition, 2022)
Background Muscle mass loss is common in long-standing rheumatoid arthritis (RA). The aim was to explore the prevalence and effects of RA disease characteristics in patients with early RA. Methods This cross-sectional study was carried out based on a Chinese RA cohort and control subjects. The body composition (BC) was assessed using bioelectric impedance analysis. Myopenia was defined by an appendicular skeletal muscle mass index of ≤ 7.0 kg/m2 in men and ≤ 5.7 kg/m2 in women. Physical dysfunction was defined as a health assessment questionnaire disability index > 1. Propensity score matching was performed to balance age and gender differences among patients with early RA (disease duration ≤ 12 months) and established RA, and controls (with 1:3:3 matching). Results In total, 2017 controls and 1,008 patients with RA were recruited for this study. Among the patients with RA, there were 190 (18.8%) patients with early RA, with a median disease duration of 7 (4, 11) months. The matched patients with early RA (n = 160) showed a higher prevalence of myopenia than the matched controls (41.3 vs. 15.8%, P < 0.0167), but no difference was found in the matched patients with established RA (41.3 vs. 50.4%, P > 0.0167). Compared with the patients with established RA, the patients with early RA exhibited higher disease activity scores [disease activity score in 28 joints with four variables including C-reactive protein (DAS28-CRP): median 4.76 vs. 3.93, P < 0.001] and a higher prevalence of physical dysfunction (26.3 vs. 19.4%, P = 0.035). In the patients with early RA, patients with myopenia showed a higher prevalence of physical dysfunction than those without myopenia (41.3 vs. 15.5%, P < 0.001), among which walking and common daily activities were the most involved subdimensions. Multivariate logistic regression analysis showed that DAS28-CRP was positively associated with myopenia [adjusted odds ratio (AOR) 1.558, 95% CI (1.138–2.132)], and myopenia [AOR 2.983, 95% CI (1.192–7.465)] was independently associated with physical dysfunction in the patients with early RA. Conclusion Our data indicate the importance of early detection of muscle involvement in the early stage of RA and imply the significance of early aggressive control of disease activity for the prevention of myopenia and physical dysfunction in patients with early RA. Our study provides a new perspective on RA management.